Environmental life cycle assessment of an on-site modular cabinet vertical farm - Martin, Michael; Bustamante, Maria J.; Zauli, Ilaria; Orsini, Francesco (Frontiers in Sustainable Food Systems, 2024)
The number of vertical farms has been expanding rapidly in recent years to provide more resilient and sustainable global food provisioning closer to consumers. However, there is a lack of empirical evidence on whether vertical farms can provide sustainable sourcing of food. The purpose of this study is to assess the environmental performance of a modular cabinet vertical farm producing lettuce and basil on-site at the end-user. To assess the environmental performance of this system, a life cycle assessment (LCA) was conducted to determine the total impact of producing lettuce and basil on-site, i.e., a kitchen for an office cafeteria, and compare to conventional sourcing.The results from this study suggest that the modular vertical farm can provide crops with environmental impacts comparable to or less than conventionally sourced options. GHG emissions ranged from 0.78-1.18 kg CO2-eq per kg lettuce and from 1.45-2.12 kg CO2-eq per kg basil from on-site production. The ranges suggest that the environmental performance is sensitive to methodological choices and life cycle inventory (LCI) data choices. These include how to treat the infrastructure for the modular cabinet, as it is often rented as a growing-service system, in addition to the LCI data choices related to the source of electricity.In conclusion, under local conditions (i.e., Stockholm, Sweden) the modular vertical farm can produce lettuce with equivalent emissions and quality to imported lettuce, despite its high energy requirement. The findings and knowledge from this study add to the growing body of literature on vertical farming, providing empirical evidence on the sustainability of an on-site commercial cabinet-based vertical farm. Such information can be used for comparisons and validation of claims in the industry, and to provide empirical evidence to this developing field.